The influence of parent–child attachment on school adjustment among the left-behind children of overseas Chinese: The chain mediating role of peer relationships and hometown identity - Zhang, Huilan; Li, Zihan; Yan, Xiaoqiu; Deng, Chunkao (Frontiers in Psychology, 2022)
Background The left-behind children of overseas Chinese are a kind of vulnerable children in the eastern coastal areas of China. Previous studies have shown that there are problems in their school adjustment. This study explored the relationship between parent–child attachment and school adaptation among the left-behind children of overseas Chinese parents, as well as the chain mediating role of peer relationships and hometown identity. Methods A total of 1,047 students in grades 3–8 from 5 schools in Zhejiang Province were selected by cluster sampling. The cross-sectional survey was compiled from the Inventory of Parent and Peer Attachment, the Adaptation subscale of the Adolescent Mental Health Quality Questionnaire–Chinese Version, the Hometown Identity Scale, and the Student Peer Relationship Scale. Structural equation modeling was used to test the conceptual model. Results The results showed that the influence of parent–child attachment on school adjustment among the left-behind children of overseas Chinese was mediated by hometown identity. Moreover, this impact was also sequentially mediated by peer relationships and hometown identity. Conclusion This study revealed peer relationships and hometown identity as underlying mechanism that explained the influence of parent–child attachment on school adjustment among left-behind children. It may provide empirical support for future interventions.